2023
DOI: 10.3390/biom13121794
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol and Resveratrol-Loaded Galactosylated Liposomes: Anti-Adherence and Cell Wall Damage Effects on Staphylococcus aureus and MRSA

Giuliana Prevete,
Beatrice Simonis,
Marco Mazzonna
et al.

Abstract: Antibiotic resistance due to bacterial biofilm formation is a major global health concern that makes the search for new therapeutic approaches an urgent need. In this context,, trans-resveratrol (RSV), a polyphenolic natural substance, seems to be a good candidate for preventing and eradicating biofilm-associated infections but its mechanism of action is poorly understood. In addition, RSV suffers from low bioavailability and chemical instability in the biological media that make its encapsulation in delivery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…For example Faezizadeh et al reported a four-fold increase in antibacterial efficacy of Silybum marianum extract against MRSA after encapsulation in liposomes formulated with egg lecithin and cholesterol (MIC of 500 mg/L for unloaded extract and 125 mg/L for extract loaded liposomes) [34] , as well as Karimi et al reported an increased antimicrobial activity of turmeric extract encapsulated in liposomes (formulated with phosphatidylcholine) compared to that of the free extract against different bacteria species [35] . For those substances that may possess several biological activities, the encapsulation in liposomes can even increase some of these properties and suppress others, as it was found for the encapsulation of trans -resveratrol (a stilbenoid polyphenol synthesized by seventy-two different plant species) in liposomes functionalized with galactosylated amphiphile, where trans -resveratrol anti-adhesive and anti-biofilm properties against S. aureus and MRSA were greatly amplified after encapsulation while its bacteriostatic properties was completely knocked down [36] .…”
Section: Introductionmentioning
confidence: 97%
“…For example Faezizadeh et al reported a four-fold increase in antibacterial efficacy of Silybum marianum extract against MRSA after encapsulation in liposomes formulated with egg lecithin and cholesterol (MIC of 500 mg/L for unloaded extract and 125 mg/L for extract loaded liposomes) [34] , as well as Karimi et al reported an increased antimicrobial activity of turmeric extract encapsulated in liposomes (formulated with phosphatidylcholine) compared to that of the free extract against different bacteria species [35] . For those substances that may possess several biological activities, the encapsulation in liposomes can even increase some of these properties and suppress others, as it was found for the encapsulation of trans -resveratrol (a stilbenoid polyphenol synthesized by seventy-two different plant species) in liposomes functionalized with galactosylated amphiphile, where trans -resveratrol anti-adhesive and anti-biofilm properties against S. aureus and MRSA were greatly amplified after encapsulation while its bacteriostatic properties was completely knocked down [36] .…”
Section: Introductionmentioning
confidence: 97%